(untitled) (Mandaluyong City, Philippines, 2009)
Contents: Fundamental isues of catastrophe risk finance in Asia and the Pacific; Applications of catastrophe risk transfer mechanisms in Asia and the Pacific; Areas for consideration...
Keywords: Disaster insurance,Bảo hiểm thiên tai; Risk management,Quản lý rủi ro; Asia,Châu Á